New-onset atrial fibrillation after percutaneous coronary intervention or coronary artery bypass grafting for left main disease - Harun Avdagić; Ivana Iveljić; Elmir Jahić; Selma Sijerčić; Alisa Krdžalić; Amar Skakić; Jasenko Radović; Emir Ahmetašević (Medicinski glasnik, 2019)
Aim: To determine the prevalence of new-onset atrial fibrillation (NOAF) following percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) for left main coronary artery disease (LMCAD) and its effect on 6-month cardiovascular outcomes. Methods: This prospective study included 40 patients diagnosed with LMCAD, in the period from 2017 to 2018. The patients with LMCAD and low or intermediate SYNTAX score were randomized to PCI with zotarolimus-eluting stents versus CABG. Outcomes were analyzed according to the development of NOAF during the initial hospitalization following revascularization. Results: Among 40 patients without atrial fibrillation on presentation, NOAF developed 3.1±1.3 days during hospitalization in three CABG treated patients, and one PCI treated patient. One patient that was CABG treated developed NOAF after two months. Patients with versus patients without NOAF had a significantly longer duration of hospitalization, probably because they were discharged on anticoagulant therapy. Myocardial infarction was presented in one CABG treated patient after 3 months, and also in one PCI treated patient after 4 months. One patient died 2 months after the operation, and one developed stroke 5 months after the CABG operation. Conclusion: The NOAF was common after CABG, but extremely rare after PCI, and it occurred almost exclusively following CABG. There was a clear statistical tendency for all-cause death, cardiovascular death and stroke at 6-month follow-up period.
Keywords: atrial fibrillation; coronary artery disease; coronary bypass surgery; percutaneous coronary intervention; prognosis